2009
DOI: 10.1080/15440470802700238
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Spinning Enzyme-Retted Flax Fibers

Abstract: Flax (Linum usitatissimum L.) fibers can be blended with other short staple fibers, such as cotton (Gossypium barbadense L. or Gossypium hirsutum L.), processed into a yarn, and then manufactured into a fabric. Enzyme-retting is a new, experimental method that decomposes the pectinaceous and matrix substances to separate cellulose fibers from shives using pectinase-rich enzymes and chelators. Spinning tests were used to determine how well fibers were assembled to form yarn and provided an indirect measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Chelator level alone did not affect strength. Fibers from this study were blended with cotton (50 : 50), spun as yarn in a miniature spinning system, and the yarn properties determined [ 118 ]. Results indicated that enzyme treatments affected yarn properties, with the highest enzyme level producing finer fibers, easier yarn construction, and better quality yarns.…”
Section: Retting Of Stems For Fiber Extractionmentioning
confidence: 99%
“…Chelator level alone did not affect strength. Fibers from this study were blended with cotton (50 : 50), spun as yarn in a miniature spinning system, and the yarn properties determined [ 118 ]. Results indicated that enzyme treatments affected yarn properties, with the highest enzyme level producing finer fibers, easier yarn construction, and better quality yarns.…”
Section: Retting Of Stems For Fiber Extractionmentioning
confidence: 99%
“…These efforts have been documented in numerous papers [5][6][7][8] and in the book The Biology and Processing of Flax [9]. Enzymatic scouring of linen fabric with use biopreparations for example Bioprep, Flaxzyme from Novozymes (North America) [10,11] and other analogs [12,13] is insufficiently described. New approaches to the development of a biochemical pretreatment process, leading to an improvement of the finishing technology through its unification, are formulated in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…However, flax fiber has some characteristics unfavorable to spinning, such as more nep and high rigidity, which could lead to the more hairiness, low strength, and bad evenness of flax ring-yarn [4,5]. The physical properties of flax fiber are given in Tab.…”
Section: Introductionmentioning
confidence: 99%